Qualidade jornalística : uma avaliação dos indicadores pluralidade e confiabilidade no jornalismo literário da Revista piauí - Santos, Egicyane Lisboa Farias (2017)
This research project is concerned with evaluating the reliability and plurality of the reports produced by Revista piauí (piauí Journal) within the perspective of literary journalism for the purpose of evaluating its editorial quality applying the reliability and plurality matrix. Before performing the application of the matrix to which the work is proposed, however, it is necessary to deepen the treatment of literary journalism, which is characterized by the aim of quality in its matters, often making the production process more time consuming, by increasing the resources of journalism. And it differs from factual journalism by claiming a more detailed description of reality, the scene-by-scene construction, dialogues, characterization of the characters, habits, manners, more dense and complete capture of reality that the story reproduces. In addition to exercising the literary vein in a journalistic text and being a genre that seeks perpetuity and depth to the reports, without a pre-established control in the size of the text presenting information in a more creative way. We also approach reliability and plurality with quality requirements, pointing to possibilities of verification, within an editorial quality evaluation proposal that reflects commitments regarding media accountability. The term accountability is linked to the ability to ascertain and collect responsibility and transparency in the fulfillment of certain obligations, whether legal or moral. Although social responsibility is essential for monitoring systems, what matters most to accountability studies is not the social responsibility itself, but the ability to verify its effective compliance. Soon after, we approach the plurality indicator, which suggests to present great varieties of opposing points of view, besides being conceptualized as something independent of a political framework of a country, being an indicator of freedom of the press. The research applied and used as a basis the content analysis (Bardin 2011) from the constant categories in the reliability matrix, through journalistic production management software called Qualijor, which has, among other structures, a specific matrix for the evaluation of veracity, both evaluation instruments developed under the Program for Research in Quality, Innovation and Technology Applied to Journalism (Qualijor) at the Federal University of Sergipe – UFS. The research intended, after applying the matrix, to evaluate and reformulate when necessary its categories, scoring systems and mode of application, in order to propose adjustments and improvements, at the same time that used to evaluate the reliability and plurality of the journalistic information in the journal cited, generating reliability indexes of the evaluated articles for editorial quality purposes. The use of the software reinforced the effectiveness of the methodology, demonstrating that it is able to generate accurate evaluations and detailed data.